Penggunaan Hashtag #KaburAjaDulu dalam Pembentukan Algoritma Kritik Publik di Media Baru - Tumanggor, Timur; Sazali, Hasan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study examines the use of hashtags #kaburajadulu as a form of public criticism that is formed and spread through social media algorithms. This hashtag represents the emotional and collective response of people, especially the younger generation, to economic pressures, social inequality, and structural injustice. With a qualitative approach through non-participatory observation and web scraping on platform X (formerly Twitter), the analysis was carried out using Entman's (1993) framing model to identify the narrative construction, the causes of the problem, the moral evaluation, and the form of symbolic solutions offered by netizens. The findings suggest that #kaburajadulu act as an advocacy medium and a digital social therapy space that strengthens emotional solidarity. Additionally, social media algorithms contribute to expanding the reach and pervasiveness of hashtags, making them an effective digital protest tool. This research fills a gap in the literature by highlighting the relationship between public expression of anxiety and the algorithmic mechanisms that determine the visibility of criticism in the digital space. Therefore, viral hashtags such as #kaburajadulu cannot be seen as a momentary phenomenon, but rather as a representation of the construction of collective discourse in the era of algorithm-based communication.